Batch ethanol fermentation using glucose derived from tapioca flour starch by Saccharomyces Cerevisiae for effect of temperature and agitation rate - Mohd Azimie, Ahmad (2008)
Bioethanol can be produced from amylose and amylopectin that originate from various sources of biomass. This study was focusing on the production of ethanol from glucose derived from tapioca flour starch using Saccharomyces cerevisiae. The objectives of this study are to determine the yield of ethanol produced from certain amount of tapioca flour, the effects of the fermentation temperature and agitation speed in fermentation process. Enzymatic process is purposely done to convert the tapioca flour starch to its glucose. Two types of enzyme were employed for these processes which were α-amylase and amyloglucosidase. This study is done in batch mode of aerobic fermentation process. The temperature and agitation used in this experiment are 30, 35, 37°C and 100, 200, and 300 rpm. Determination of cell growth concentration in inoculation process plays an important role to ensure the microbial activity and determination of microbe growth. Results show that yield of ethanol production will increase as the temperature and agitation increase until it reaches the optimum point. From this study, it was observed that optimum condition for ethanol fermentation by Saccharomyces cerevisiae was at 35°C with agitation speed of 200 rpm.